β-Lactam Allergy and Cross-Reactivity: A Clinician’s Guide to Selecting an Alternative Antibiotic - Caruso, Cristiano; Valluzzi, Rocco Luigi; Colantuono, Stefania; Gaeta, Francesco; Romano, Antonino (Journal of asthma and allergy, 2021)
β-Lactams which include penicillins, cephalosporins, carbapenems, and monobactams are the most common antibiotic classes reported to cause allergic reactions to drugs. This review is mainly about published studies assessing the cross-reactivity among β-lactams in penicillin- or cephalosporin-allergic subjects by carrying out diagnostic tests with alternative β-lactams and, if appropriate, graded challenges. Several studies demonstrated that cross-reactivity connected with the β-lactam ring, causing positive responses to allergy tests with all β-lactams, is infrequent in subjects with an IgE-mediated allergy and anecdotal in those with a T-cell-mediated allergy. Identities or similarities of β-lactam side-chain structures are mainly responsible for cross-reactivity among these antibiotics. For example, in aminopenicillin-allergic subjects, cross-reactivity with aminocephalosporins could possibly be over 30%. On the other hand, in a few prospective studies of penicillin-allergic individuals, less than 1% of cases show a cross-reactivity between penicillins and both aztreonam and carbapenems. Particular patterns of allergy-test positivity observed in some studies that assessed cross-reactivity among β-lactams seem to indicate that prior exposures may be responsible for coexisting sensitivities. Therefore, pre-treatment skin tests with the related β-lactams are suggested before administering them via graded challenges to β-lactam-allergic patients who need alternative β-lactams.